1991
DOI: 10.1093/oxfordjournals.eurheartj.a059829
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic visualization of ‘tumour vascularity’ in atrial myxoma

Abstract: Nine patients with atrial myxoma in whom selective coronary arteriography had been performed were studied. The angiographic sign of 'tumour vascularity' was found to be present in three patients with highly vascularized atrial myxoma. The clinical significance of the angiographic sign is unknown although highly vascularized myxomata appear to have a greater propensity to bleeding into the tumour, resulting in an acute worsening of clinical symptoms. The angiographic sign of 'tumour vascularity' is not specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Review of the first coronary angiography showed a single-vessel disease with a thrombus-like formation in the proximal third of the LAD coronary artery. This lesion still present on the angiography 3 years later, From our experience and the data published by Fueredi et al [14] and Chow et al [15], the prevalence of angiographically visible neovascularity in symptomatic cardiac myxomas is about 40 percent (15 of 37 patients).…”
Section: Discussionsupporting
confidence: 56%
“…Review of the first coronary angiography showed a single-vessel disease with a thrombus-like formation in the proximal third of the LAD coronary artery. This lesion still present on the angiography 3 years later, From our experience and the data published by Fueredi et al [14] and Chow et al [15], the prevalence of angiographically visible neovascularity in symptomatic cardiac myxomas is about 40 percent (15 of 37 patients).…”
Section: Discussionsupporting
confidence: 56%
“…To the best of our knowledge, there are only five studies in the literature investigating the relationship between CAD and myxoma [8, 9, 13, 14, 15] (table 4). Most of those studies showed prevalence rates of CAD in myxoma patients of 0–11%, and only the study performed by Fueredi et al [9]yielded a very high (6/9, 66.7%) rate.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography is sometimes helpful in visualizing the vascular supply of the neoplasm and the relation of the neoplasm to the coronary arteries. The angiographic sign of 'tumor vascularity' was found to be present in some patients with highly vascularized atrial myxomas [55,56]. The vascular pattern is not helpful, however, in differentiating benign from malignant tumors.…”
Section: Angiographymentioning
confidence: 99%